IN-VIVO BIOSTABILITY AND CALCIFICATION-RESISTANCE OF SURFACE-MODIFIED PU-PEO-SO3 - HAN, DK; PARK, KD; JEONG, SY; KIM, YH; KIM, UY; MIN, BG (JOHN WILEY & SONS INC, 1993)
To examine the biostability and calcification-resistance of polyurethanes (PUs), the surface of PU was grafted with hydrophobic perfluorodecanoic acid (PFDA) (PU-PFDA), hydrophilic polyethyleneoxide (PEO) (PU-PEO1000), and further negatively charged sulfonate groups (PU-PEO1000-SO3). An in vivo animal test was conducted by subcutaneous implantation in rats during 2, 4 and 6 months. A scanning electron microscope study demonstrated that the degree of surface cracking on explanted PUs was increased in the following order: PU-PFDA > PU > PU-PEO1000 > PU-PEO1000-SO3. In the results of energy dispersive x-ray analysis and inductively coupled plasma atomic emission spectrometry, the deposition of calcium was found abundantly, but that of phosphorus was hardly in existence in all implanted PUs, suggesting that this calcium compound is not a hydroxyapatite. The calcium contents, regardless of implantation time, were also increased in the same order (PU-PFDA > PU > PU-PEO1000 > PU-PEO1000-SO3). After 6 months implantation, no severe tissue reactions were observed and calcification almost occurred on polymer surfaces in all implants. Such superior biostability and anticalcification of PU-PEO1000-SO3 might be attributed to synergistic effects of its excellent surface smoothness, sulfonate acid (SO3-) groups, nonadhesive and mobile PEO, and the high hydrophilicity and enhanced blood compatibility. Therefore, PU-PEO1000-SO3 is promising as biostable and calcification-resistant biomaterial. (C) 1993 John Wiley & Sons, Inc.